Increasing the Results of Bullet Rejection Skills Using the Jigsaw Learning Method - Toriquddin lutfi; Fauzi Muhamad; Pamungkas Hari; Yogidarso Termiantono; Rahmadhani Hafid; Dianto Mochamad; Juriyah Juriyah (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
This study aims to evaluate the impact of using the Jigsaw learning method in improving students' shot put skill outcomes. The Jigsaw method is applied in a classroom environment to facilitate group collaboration, where students are given the responsibility to learn a particular aspect of the shot put technique and then teach it to the rest of the group. The study involved observation of the learning process, evaluation of skill progress, and analysis of student responses using the PTK (class action research) method to students SMK Tamansiswa, Mojoagung, Kab. Jombang, with a total of 38 students. The results showed a significant improvement from the pre-cycle which was complete 5 students with 13.2%, incomplete 33 students and 86.8%. In cycle 1, 13 students with 34.2% were complete, while 25 students with 65.8% were incomplete. In cycle 2 100%, in students' in-depth understanding of the shot put technique, increased collaboration between students, and higher learning motivation. These results highlight the potential of the Jigsaw method as an effective approach in improving classroom skills in the sport of shot put. This study provides a foundation for further integration of collaborative learning methods in the context of teaching sport in schools